Les variants informels de très - Holló, Zsuzsanna (Verbum – Analecta Neolatina, 2009)
The aim of this paper is to analyse the adjectival collocations of French adverbs of degree synonymous with très 'very' and typical of what is referred to as "familiar style". While a number of studies were written on English adjective–adverb co-occurrences, French researches fall short of them. Our examples are retrieved fromliterary fiction covering the 20th century, using the Frantext database. After finding thirteen synonymous adverbs of degree on the basis of different dictionaries, we examine their collocational behaviour occurring in recurrent combinations. We include the types and the tokens of their adjectival collocatives and we show thatmost of themtend to be associated with general, positive adjectives. Mutual information (MI) measure has found the most frequently occurring collocations among the synonymous combinations. We also show that the collocations appear in diverse syntactic structures.